Comparative study of the quality of life of children and adolescents from schools of Lima and Ancash - Sotelo López, Noemí (2013)
They are considered Shalock approaches according to quality of life, whereas indicators both for children and for adolescents. Objective: determine if there are differences in the quality of life in children and adolescents from schools of Lima and Ancash. Method: It assessed a total of 307 children and 347 adolescents between 8 and 18 years of Lima and Ancash, through the questionnaire of quality of life for adolescents and questionnaire of quality of life for children.Results: are reported significant differences between children of Lima and Ancash in relation to quality of life indicators, and adolescents in Lima and Ancash, in the personal development and well-being Material dimensions. Conclusion: The indicators will form the basis for proposals to improve the deficit areas and to enhance that are helping people.